Characterization of the complete chloroplast genome of Alsophila spinulosa, an endangered species endemic to China. Issue 3 (2nd July 2020) - Ma, Yiyong; Jiao, Peng; Qi, Zhuo; Jiang, Zhenzhong; Guan, Shuyan
Abstract: Tree fern Alsophila spinulosa is an endangered relic plant in the world. It is currently on the International Union for Conservation of Nature (IUCN) red list of threatened species. In this study, we first assembled the complete chloroplast (cp) genome of A. spinulosa by Illumina paired-end reads data. The whole genome was 156, 661 bp, consisting of a pair of inverted repeats of 24, 364 bp, large single copy region and a small single copy region (70, 352 and 21, 624 bp in length, respectively). The cp genome contained 133 genes, including 92 protein-coding genes, 33 trRNA genes, and eight rRNA genes. The overall GC content of the whole genome was 40.4%. A neighbour-joining phylogenetic analysis demonstrated a close relationship between A. spinulosa and Cystoathyrium chinense Ching.